2022
DOI: 10.3390/s22031018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation for Magnetoelectric Sensor Systems in Biomagnetic Diagnostics

Abstract: Dedicated research is currently being conducted on novel thin film magnetoelectric (ME) sensor concepts for medical applications. These concepts enable a contactless magnetic signal acquisition in the presence of large interference fields such as the magnetic field of the Earth and are operational at room temperature. As more and more different ME sensor concepts are accessible to medical applications, the need for comparative quality metrics significantly arises. For a medical application, both the specificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In addition to determining the ME voltage coefficients for magnetostrictive–piezoelectric structures for the quasi‐static mode and in the region of the longitudinal EMR mode, the nomogram method can also be used to study the ME effect in the microwave region. [ 10 ] Similarly, previously obtained expressions for the microwave region can be used to construct nomograms and further used for their intended purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to determining the ME voltage coefficients for magnetostrictive–piezoelectric structures for the quasi‐static mode and in the region of the longitudinal EMR mode, the nomogram method can also be used to study the ME effect in the microwave region. [ 10 ] Similarly, previously obtained expressions for the microwave region can be used to construct nomograms and further used for their intended purpose.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] The parameters of the ME composite can be changed by changing the composition of the magnetic and electric phases, or by changing the orientation of the applied magnetic and electric fields. As a result, a large number of new ME effect-based devices, such as sensors, gyrators, antennas, harvesters, and microwave devices, [3][4][5][6][7][8][9][10][11][12] have been proposed in a wide frequency range. The basis of any ME device is a sensitive element, i.e., an ME composite, and the characteristics of the ME device greatly depend on its parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the feasibility of a pickup coil as a sensor unit for MPI applications [ 9 , 15 , 16 ]. Magnetoelectric composites have extensive applications as mechanical actuators [ 17 ] and magnetic sensors [ 18 , 19 ] due to high sensitivity and a reasonable limit of detection for medical applications [ 20 ]. A recently developed MPM approach has been introduced by utilizing the ME sensor as a detection unit [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The great interest in this device is because, having a simple three-layer Metglas-PMN-PT-Metglas structure, in the near future it can replace a complex electronic device such as a SQUID operating at helium temperature, since comparable values for giant ME voltage coefficient of 4.26 × 10 4 V cm −1 Oe −1 and the equivalent magnetic noise of 2.89 fT Hz −1/2 at EMR frequency on this structure have already been achieved. If we consider its small weight and size parameters and operation at room temperature, then we can expect widespread use of the ME magnetic field sensor in areas such as biomedicine [37][38][39]. Next, we should briefly emphasize the main characteristics of other new ME devices, in which they can compete with well-known serial devices.…”
Section: Introductionmentioning
confidence: 99%